1999
DOI: 10.1182/blood.v93.11.3624.411a28_3624_3631
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cell Adhesion by Antibodies to Arg-Gly-Asp (RGD) in Normal Immunoglobulin for Therapeutic Use (Intravenous Immunoglobulin, IVIg)

Abstract: Intravenous immunoglobulin (IVIg) therapy is associated with a broad range of immunomodulatory activities. Several of the postulated mechanisms of IVIg action relate to the presence of antibodies to molecules relevant for regulation of the immune response. This article reports that IVIg contains antibodies to the Arg-Gly-Asp (RGD) sequence, and the attachment site of a number of adhesive extracellular matrix proteins, including ligands for β1, β3, and β5 integrins. Anti-RGD antibodies were identified in IVIg b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…Many of the integrins share affinity towards the RGD recognition sequence (the Arg-Gly-Asp motif) in their extracel-lular matrix ligand and are able to discriminate between different RGD-containing proteins. We have shown that IVIG contains antibodies that bind to human RGD-containing integrin ligands [91]. The biological relevance of anti-RGD antibodies in IVIG was demonstrated by their ability to inhibit B-lymphocyte adhesion to fibronectin.…”
Section: Inhibition Of Cell Adhesionmentioning
confidence: 99%
“…Many of the integrins share affinity towards the RGD recognition sequence (the Arg-Gly-Asp motif) in their extracel-lular matrix ligand and are able to discriminate between different RGD-containing proteins. We have shown that IVIG contains antibodies that bind to human RGD-containing integrin ligands [91]. The biological relevance of anti-RGD antibodies in IVIG was demonstrated by their ability to inhibit B-lymphocyte adhesion to fibronectin.…”
Section: Inhibition Of Cell Adhesionmentioning
confidence: 99%
“…IVIG has also been shown to reduce adhesion of T cells to extracellular matrix following activation by phytohaemagglutinin (PHA) or phorbol myristate acetate (PMA) [13] and contains antibodies to the Arg-Gly-Asp (RGD) motif, the attachment site for a number of adhesive extracellular matrix proteins and b 1, b 3 and b 5 integrins [14].…”
Section: Effects Due To F(ab¢ ¢ ¢ ¢ )mentioning
confidence: 99%
“…The spectrum of self-antigens to which these antibodies bind, their fate after intravenous infusion and their biological activity remain a matter of controversy. We (14)(15)(16), as well as others (17), have previously suggested that natural IgG autoantibodies specific to lymphocyte surface molecules may be partially responsible for the beneficial immunomodulatory effects of IVIg in autoimmune patients.…”
mentioning
confidence: 81%
“…It was cultured in the peritoneum of pristane-pretreated SCID mice (obtained from Iffa Credo, L'Arbresle, France) and the pure antibody was obtained from their ascitic fluid. F(ab¢) 2 fragments were prepared from the IVIg preparation and from the M061 monoclonal antibody as previously described (15).…”
Section: Immunoglobulin Preparations and Monoclonal Antibodymentioning
confidence: 99%